PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN PADA MANDIRI TUNAS FINANCE PURWOKERTO - Esti Saraswati (Jurnal Ilmu Akuntansi, 2021)
Business competition which is increasingly rapidly in the era of globalization has occurred in the trading company sector, service companies, and manufacturing companies. Service companies engaged in non-bank financial institutions such as the multi-finance industry are also experiencing quite rapid business competition which requires the use of accounting information systems in all operational and non-operational activities of the company. Employee performance is a measure of the success of a company. With the existence of an adequate Accounting Information System, various financial and non-financial information can be produced quickly and accurately so that management and employees will be assisted during the decision-making process. Apart from the existence of an adequate accounting information system, the existence of internal controls within the company is no less important for the creation of a company system and good employee performance. This study aims to determine how the influence of accounting information systems and internal controls on employee performance. The population in this study were employees of Mandiri Tunas Finance Purwokerto. To determine the sample in this study, the Simple Random Sampling technique was used. The type of data used in the study is primary data obtained by distributing questionnaires to respondents. The results of this study indicate that the accounting information system has no effect on employee performance, while internal control has an effect on employee performance.